2020
DOI: 10.9734/ajfar/2020/v9i230154
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Partial Replacement of Fishmeal with Leucaena leucocephala Leaf Meal on the Growth Performance of Tilapia zilli Fingerlings

Abstract: Aims: A study was carried out to determine the effect of replacing fishmeal with Leucaena leucoephala leaf meal in the diet of Tilapia zilli fingerlings. Study Design: Three hundred (300) Tilapia zilli fingerlings (9.5±0.5 g/fish, mixed sex) fed with diet containing Leucaena leucoephala leaf meal for 10 weeks at 0%, 2.5%, 5.0%, 7.5% and 10.0% level of inclusion, representing the replacement of fish meal at 0%, 25% 75% and 100% respectively. Place and Duration of Study:  A study was carried out in t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
3
1

Year Published

2022
2022
2022
2022

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 5 publications
(12 reference statements)
0
3
1
Order By: Relevance
“…The crude fibre reported in this current study was higher than the 13.85% reported by Adedeji et al (2013) but lower than 19.20 reported in the work of Babalola and Fakunmoju (2020). The improved crude fibre in the tested leaf meal can aid in bowel movement, favoring nutrient absorption and reducing constipation (Lunn and Buttriss 2007;Amobi et al 2019).…”
Section: Discussioncontrasting
confidence: 61%
See 1 more Smart Citation
“…The crude fibre reported in this current study was higher than the 13.85% reported by Adedeji et al (2013) but lower than 19.20 reported in the work of Babalola and Fakunmoju (2020). The improved crude fibre in the tested leaf meal can aid in bowel movement, favoring nutrient absorption and reducing constipation (Lunn and Buttriss 2007;Amobi et al 2019).…”
Section: Discussioncontrasting
confidence: 61%
“…de Wit, commonly known as Leucaena or white leadtree is one of the suitable plant protein alternatives to fishmeal for fish feed due to its medium-high protein content, suitable levels of amino acids and most importantly, very affordable market price tag (De Angelis et al 2021). However, few studies have demonstrated that Leucaena leaf meal can successfully replace fishmeal as a protein source in fish diets at different inclusion levels (Bairagi et al 2004;Tiamiyu et al 2015;Babalola and Fakunmoju 2020).…”
Section: Introductionmentioning
confidence: 99%
“…The efficiency of feeding is directly proportional to the addition of body weight, so the higher the value of feeding efficiency means the more efficient the fish use the feed consumed for growth [10]. The feed can be said to be good if the feeding efficiency value is more than 50% or even close to 100% [11].…”
Section: Results and Discussion A Feed Efficiencymentioning
confidence: 99%
“…The effect of using Leucaena leaf meal in this study established that it could be used at recommended level of inclusion in the fish diet. the use of plant protein, But the used of Leucaena leaf meal to replace animal protein in the diet of Tilapia zilli fingerlings in order to reduce competition between man and animal which often times precede the scarcity and over prizing of it as emphasized by [19].…”
Section: Effect Of Ipil-ipil (Leucaena Leucocephala) As Fish Feedmentioning
confidence: 99%